Analysis Of Riba in Household Consumer Debt Among The Community Of Sindanghaji Village - lestari, Ayu Gumilang; Rendy Muhammad Susilo, Aa; Reza Abdul Aziz, Faisal; Rahayu , Sinta; Magfirah , Siti; Rusmiyati, Kurnia (Prodi Ekonomi Syariah Universitas Majalengka, 2024)
This study explores the impact of consumptive debt practices involving usury (riba) in the community of Sindanghaji Village, Majalengka Regency, Indonesia. Amidst rapid economic growth and increasing inequality, rural communities face difficulties in meeting their basic needs, leading them to resort to borrowing from financial institutions such as